Marketing research for the tourism, hospitality and events industries - Kolb, Bonita M. (London Routledge, 2018)
This is a user-friendly textbook that covers qualitative, quantitative and social media methods, providing tourism, hospitality and events students and course leaders with an accessible guide for learning and teaching marketing research. The book contains essential information on how to conduct research on visitor trends, experiences, preferences and lifestyles, shedding light on customer preferences, product changes, promotional efforts and pricing differences to ensure the destination is successful. It offers guidance on how to write, conduct and analyze the results of surveys, or use qualitative methods such as focus groups, interviews, projective techniques and observation. It also illustrates how social media can be used as a new means to determine visitor preferences by analyzing online data and conversations. Other content includes suggestions and examples on turning research data into actionable recommendations as well as advice on writing and presenting the final report. Integrated with a wide range of case studies per chapter, this short and accessible textbook is essential reading for all students wishing to gain knowledge as to what visitors want from the travel, hospitality and/or event experience.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Tourism -- Research -- Methodology -- Textbooks; Hospitality industry -- Research -- Methodology -- Textbooks; Entertainment events -- Research -- Methodology -- Textbooks; Marketing research -- Methodology -- Textbooks